2011
DOI: 10.1136/thx.2010.153288
|View full text |Cite
|
Sign up to set email alerts
|

The importance of ultrasound in staging and gaining a pathological diagnosis in patients with lung cancer--a two year single centre experience

Abstract: Background Initial studies on the use of ultrasound in the detection and sampling of supraclavicular lymph nodes in patients with suspected lung cancer show this to be a promising technique, giving both a cytological diagnosis and pathological N3 (pN3) stage. Leicester published its initial experience in 2005 and the aim of this study was to establish if this had been embedded into the diagnostic pathway, and further to examine the use of ultrasound in diagnosing and staging lung cancer by imaging other areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…FNA of extrathoracic lymph nodes can even be performed outside of a dedicated operating theatre at the patient's bedside [10].…”
Section: Extrathoracic Lymph Nodesmentioning
confidence: 99%
See 1 more Smart Citation
“…FNA of extrathoracic lymph nodes can even be performed outside of a dedicated operating theatre at the patient's bedside [10].…”
Section: Extrathoracic Lymph Nodesmentioning
confidence: 99%
“…Air bronchograms appear as dynamic echogenic branches and foci that fluctuate with the respiratory cycle [1][2][3]5]. Fluid bronchograms are seen as anechoic tubular structures and represent fluid-filled airways [2,10]. Furthermore, ultrasonography is ideally suited to screen for parapneumonic effusions and to differentiate dense consolidation from pleural effusions in critically ill patients ( fig.…”
Section: Pulmonary Pathologymentioning
confidence: 99%
“…Drowned lung is considered to represent accumulated secretions and is typified on US by fluid bronchograms, provided it extends to the pleura (8). USassisted TTFNA of a drowned lung can be diagnostic in almost 75% of cases, and it may represent a viable alternative to bronchoscopy in selected cases (53,54).…”
Section: Transthoracic Biopsy Of Chest Wall and Pulmonary Tumorsmentioning
confidence: 99%
“…One study from a single centre lung cancer registry showed that 14.4% of patients were diagnosed with US-guided samples from either pleura, supraclavicular nodes or distant metastatic disease [57]. Another prospective study in patients suspected for thoracic malignancy showed that 13% of diagnoses were obtained with percutaneous US-guided biopsies or aspirations without the need for other invasive tests.…”
Section: Us As a Sampling Guidementioning
confidence: 99%